2022
DOI: 10.1021/acs.jpca.1c09336
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Metathesis Catalyzed by a Hoveyda–Grubbs-like Complex Chelated to Bis(2-mercaptoimidazolyl) Methane: A Predictive DFT Study

Abstract: Although highly selective complexes for the cross-metathesis of olefins, particularly oriented toward the productive metathesis of Z -olefins, have been reported in recent years, there is a constant need to design and prepare new and improved catalysts for this challenging reaction. In this work, guided by density functional theory (DFT) calculations, the performance of a Ru-based catalyst chelated to a sulfurated pincer in the olefin metathesis was computationally assessed. The catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…The phenyl group in A can acquire either a contracted or an expanded conformation. Similarly to our previous research findings, it has been demonstrated that the destabilization of OC intermediates is correlated with the destabilization of transition states . Therefore, we investigated the initiation phase exclusively for the most stable conformers.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The phenyl group in A can acquire either a contracted or an expanded conformation. Similarly to our previous research findings, it has been demonstrated that the destabilization of OC intermediates is correlated with the destabilization of transition states . Therefore, we investigated the initiation phase exclusively for the most stable conformers.…”
Section: Resultsmentioning
confidence: 55%
“…Similarly to our previous research findings, it has been demonstrated that the destabilization of OC intermediates is correlated with the destabilization of transition states. 65 Therefore, we investigated the initiation phase exclusively for the most stable conformers. Consequently, we suggest the criterion of ΔG rel < 3 kcal/mol to select the intermediates that undergo a kinetically favored initiation phase, which in this study are all OC A intermediates characterized by the expanded configuration of phenyl in A.…”
Section: Resultsmentioning
confidence: 99%
“…From Scheme 2, starting with the imine based chelate precatalyst A , and finishing with the ylidene 14e active species F , the mechanism is somewhat analogous with respect to the Hoveyda–Grubbs catalysts, 54 with the replacement of the oxygen atom bonded to ruthenium by nitrogen. 55 Before a detailed structural and electronic analysis of the set of catalysts under analysis, the energetic values for the reaction pathway of the activation are included in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the progress of the reactions was monitored by varying the dihedral angle in the case of o-OiPr-benzylidene rotation. [55] Electronic energies were obtained from the single-point M06-D3 calculations [56] including a triple ζ basis set plus polarization and diffuse functions, 6-311G + + (d,p) (standard LACV3P + + ** keyword in Jaguar). Solvent effects were included through the Poisson-Boltzmann self-consistent polarizable continuum model (PB-PCM), with toluene as the solvent.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Transition states and connecting local minima were searched by means of linear‐transit calculations using the same DFT method. Specifically, the progress of the reactions was monitored by varying the dihedral angle in the case of o ‐O i Pr‐benzylidene rotation [55] . Electronic energies were obtained from the single‐point M06‐D3 calculations [56] including a triple ζ basis set plus polarization and diffuse functions, 6–311G++(d,p) (standard LACV3P++** keyword in Jaguar).…”
Section: Computational Detailsmentioning
confidence: 99%